Thermoluminescence characteristics of silicon optical fibre doped with ytterbium and ytterbium – terbium as photon dosimeter - Sahini, Mohd. Hilmi (2014)
The study of SiO2 commercial optical fiber explores the useful thermoluminescence (TL) properties and reveals its potential as a TL dosimeter. The present work describes the TL dose response, reproducibility, fading and minimum detectable dose of SiO2: Yb and SiO2: Yb, Tb optical fibers as compared to TLD-100. The optical fibers were placed in a solid phantom and irradiated with 6 and 10 MV X-rays using LINAC Primus MC 3339 and 1.25 MeV gamma ray from gamma cell. Scanning electron microscopy analysis was performed to determine the dopant concentration and the effective atomic number, Zeff. The dopant concentration of Yb for SiO2: Yb optical fiber was found ranging between 0.23 – 0.35 mol% and for SiO2: Yb, Tb; the dopant concentration of Yb and Tb were in the range of 0.03 – 1.46 mol% and 0.12 – 0.39 mol% respectively. The Zeff value for SiO2: Yb and SiO2: Yb, Tb were 11.19 and 12.27 respectively, which is higher than that of soft tissue (7.42), but close to bone (11.6 – 13.8). In term of TL dose response and sensitivity, SiO2: Yb, Tb optical fiber demonstrated better results than SiO2: Yb optical fiber, but both TL materials were still inferior when compared to TLD-100. SiO2: Yb, Tb optical fiber had the lowest percentage lost in fading of about 5.83%, 15.65% and 18.55% for day 7, 21 and 28 respectively, compared to SiO2: Yb optical fiber which has higher fading of about 55.17% and 95.87% for day 14 and 30 respectively. SiO2: Yb, Tb optical fiber shows good reproducibility results compared to SiO2: Yb optical fiber. The minimum detectable dose of SiO2: Yb and SiO2: Yb, Tb optical fibers were 333 mGy and 19 mGy respectively. In general, it can be concluded that SiO2: Yb, Tb optical fiber is a much better optical fiber to be developed as a new TL dosimeter compared to SiO2: Yb optical fiber.